A homozygous founder mutation in associates with a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features. - Marin-Valencia, Isaac; Novarino, Gaia; Johansen, Anide; Rosti, Basak; Issa, Mahmoud Y; Musaev, Damir; Bhat, Gifty; Scott, Eric; Silhavy, Jennifer L; Stanley, Valentina; Rosti, Rasim O; Gleeson, Jeremy W; et al. (J Med Genet, 2018)
BACKGROUND: Transport protein particle (TRAPP) is a multisubunit complex that regulates membrane trafficking through the Golgi apparatus. The clinical phenotype associated with mutations in various TRAPP subunits has allowed elucidation of their functions in specific tissues. The role of some subunits in human disease, however, has not been fully established, and their functions remain uncertain. OBJECTIVE: We aimed to expand the range of neurodevelopmental disorders associated with mutations in TRAPP subunits by exome sequencing of consanguineous families. METHODS: Linkage and homozygosity mapping and candidate gene analysis were used to identify homozygous mutations in families. Patient fibroblasts were used to study splicing defect and zebrafish to model the disease. RESULTS: We identified six individuals from three unrelated families with a founder homozygous splice mutation in , encoding a core subunit of the complex TRAPP I. Patients manifested a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features, and showed splicing defect. Zebrafish morphants replicated the human phenotype, displaying decreased head size and neuronal hyperexcitability, leading to a lower seizure threshold. CONCLUSION: This study provides clinical and functional evidence of the role of in brain development and function.
Keywords: Animals; Autistic Disorder; Epilepsy; Founder Effect; Genetic Association Studies; Homozygote; Humans; Microcephaly; Mutation; Neurodevelopmental Disorders; Phenotype; Vesicular Transport Proteins; Zebrafish

Loss of Protocadherin-12 Leads to Diencephalic-Mesencephalic Junction Dysplasia Syndrome. - Guemez-Gamboa, Alicia; Çağlayan, Ahmet Okay; Stanley, Valentina; Gregor, Anne; Zaki, Maha S; Saleem, Sahar N; Musaev, Damir; McEvoy-Venneri, Jennifer; Belandres, Denice; Akizu, Naiara; Silhavy, Jennifer L; Schroth, Jana; et al. (Ann Neurol, 2018)
OBJECTIVE: To identify causes of the autosomal-recessive malformation, diencephalic-mesencephalic junction dysplasia (DMJD) syndrome. METHODS: Eight families with DMJD were studied by whole-exome or targeted sequencing, with detailed clinical and radiological characterization. Patient-derived induced pluripotent stem cells were derived into neural precursor and endothelial cells to study gene expression. RESULTS: All patients showed biallelic mutations in the nonclustered protocadherin-12 (PCDH12) gene. The characteristic clinical presentation included progressive microcephaly, craniofacial dysmorphism, psychomotor disability, epilepsy, and axial hypotonia with variable appendicular spasticity. Brain imaging showed brainstem malformations and with frequent thinned corpus callosum with punctate brain calcifications, reflecting expression of PCDH12 in neural and endothelial cells. These cells showed lack of PCDH12 expression and impaired neurite outgrowth. INTERPRETATION: DMJD patients have biallelic mutations in PCDH12 and lack of protein expression. These patients present with characteristic microcephaly and abnormalities of white matter tracts. Such pathogenic variants predict a poor outcome as a result of brainstem malformation and evidence of white matter tract defects, and should be added to the phenotypic spectrum associated with PCDH12-related conditions. Ann Neurol 2018;84:646-655.

Biallelic mutations in the 3' exonuclease TOE1 cause pontocerebellar hypoplasia and uncover a role in snRNA processing. - Lardelli, Rea M; Schaffer, Ashleigh E; Eggens, Veerle R C; Zaki, Maha S; Grainger, Stephanie; Sathe, Shashank; Van Nostrand, Eric L; Schlachetzki, Zinayida; Rosti, Basak; Akizu, Naiara; Scott, Eric; Silhavy, Jennifer L; et al. (Nat Genet, 2017)
Deadenylases are best known for degrading the poly(A) tail during mRNA decay. The deadenylase family has expanded throughout evolution and, in mammals, consists of 12 Mg-dependent 3'-end RNases with substrate specificity that is mostly unknown. Pontocerebellar hypoplasia type 7 (PCH7) is a unique recessive syndrome characterized by neurodegeneration and ambiguous genitalia. We studied 12 human families with PCH7, uncovering biallelic, loss-of-function mutations in TOE1, which encodes an unconventional deadenylase. toe1-morphant zebrafish displayed midbrain and hindbrain degeneration, modeling PCH-like structural defects in vivo. Surprisingly, we found that TOE1 associated with small nuclear RNAs (snRNAs) incompletely processed spliceosomal. These pre-snRNAs contained 3' genome-encoded tails often followed by post-transcriptionally added adenosines. Human cells with reduced levels of TOE1 accumulated 3'-end-extended pre-snRNAs, and the immunoisolated TOE1 complex was sufficient for 3'-end maturation of snRNAs. Our findings identify the cause of a neurodegenerative syndrome linked to snRNA maturation and uncover a key factor involved in the processing of snRNA 3' ends.
Keywords: Alleles; Animals; Cerebellar Diseases; Exonucleases; Female; Humans; Male; Mice; Mutation; Neurodegenerative Diseases; Nuclear Proteins; RNA, Messenger; RNA, Small Nuclear; Spliceosomes; Zebrafish

Biallelic Mutations in TMTC3, Encoding a Transmembrane and TPR-Containing Protein, Lead to Cobblestone Lissencephaly. - Jerber, Julie; Zaki, Maha S; Al-Aama, Jumana Y; Rosti, Rasim Ozgur; Ben-Omran, Tawfeg; Dikoglu, Esra; Silhavy, Jennifer L; Caglar, Caner; Musaev, Damir; Albrecht, Beate; Campbell, Kevin P; Willer, Tobias; et al. (Am J Hum Genet, 2016)
Cobblestone lissencephaly (COB) is a severe brain malformation in which overmigration of neurons and glial cells into the arachnoid space results in the formation of cortical dysplasia. COB occurs in a wide range of genetic disorders known as dystroglycanopathies, which are congenital muscular dystrophies associated with brain and eye anomalies and range from Walker-Warburg syndrome to Fukuyama congenital muscular dystrophy. Each of these conditions has been associated with alpha-dystroglycan defects or with mutations in genes encoding basement membrane components, which are known to interact with alpha-dystroglycan. Our screening of a cohort of 25 families with recessive forms of COB identified six families affected by biallelic mutations in TMTC3 (encoding transmembrane and tetratricopeptide repeat containing 3), a gene without obvious functional connections to alpha-dystroglycan. Most affected individuals showed brainstem and cerebellum hypoplasia, as well as ventriculomegaly. However, the minority of the affected individuals had eye defects or elevated muscle creatine phosphokinase, separating the TMTC3 COB phenotype from typical congenital muscular dystrophies. Our data suggest that loss of TMTC3 causes COB with minimal eye or muscle involvement.
Keywords: Alleles; Amino Acid Sequence; Basement Membrane; Brain; Carrier Proteins; Cerebellum; Cobblestone Lissencephaly; Developmental Disabilities; Dystroglycans; Eye Abnormalities; Female; Humans; Infant; Male; Membrane Proteins; Mutation; Nervous System Malformations; Neuroglia; Neurons; Pedigree; Phenotype

Biallelic mutations in SNX14 cause a syndromic form of cerebellar atrophy and lysosome-autophagosome dysfunction. - Akizu, Naiara; Cantagrel, Vincent; Zaki, Maha S; Al-Gazali, Lihadh; Wang, Xin; Rosti, Rasim Ozgur; Dikoglu, Esra; Gelot, Antoinette Bernabe; Rosti, Basak; Vaux, Keith K; Scott, Eric M; Silhavy, Jennifer L; et al. (Nat Genet, 2015)
Pediatric-onset ataxias often present clinically as developmental delay and intellectual disability, with prominent cerebellar atrophy as a key neuroradiographic finding. Here we describe a new clinically distinguishable recessive syndrome in 12 families with cerebellar atrophy together with ataxia, coarsened facial features and intellectual disability, due to truncating mutations in the sorting nexin gene SNX14, encoding a ubiquitously expressed modular PX domain-containing sorting factor. We found SNX14 localized to lysosomes and associated with phosphatidylinositol (3,5)-bisphosphate, a key component of late endosomes/lysosomes. Patient-derived cells showed engorged lysosomes and a slower autophagosome clearance rate upon autophagy induction by starvation. Zebrafish morphants for snx14 showed dramatic loss of cerebellar parenchyma, accumulation of autophagosomes and activation of apoptosis. Our results characterize a unique ataxia syndrome due to biallelic SNX14 mutations leading to lysosome-autophagosome dysfunction.
Keywords: Animals; Atrophy; Autophagy; Cerebellar Diseases; Cerebellum; Child, Preschool; Female; Gene Frequency; Humans; Infant; Lod Score; Lysosomal Storage Diseases; Lysosomes; Male; Mutation; Phagosomes; Sorting Nexins; Spinocerebellar Ataxias; Syndrome; Zebrafish

Functional genome-wide siRNA screen identifies KIAA0586 as mutated in Joubert syndrome. - Roosing, Susanne; Hofree, Matan; Kim, Sehyun; Scott, Eric; Copeland, Brett; Romani, Marta; Silhavy, Jennifer L; Rosti, Rasim O; Schroth, Jana; Mazza, Tommaso; Miccinilli, Elide; Zaki, Maha S; et al. (Elife, 2015)
Defective primary ciliogenesis or cilium stability forms the basis of human ciliopathies, including Joubert syndrome (JS), with defective cerebellar vermis development. We performed a high-content genome-wide small interfering RNA (siRNA) screen to identify genes regulating ciliogenesis as candidates for JS. We analyzed results with a supervised-learning approach, using SYSCILIA gold standard, Cildb3.0, a centriole siRNA screen and the GTex project, identifying 591 likely candidates. Intersection of this data with whole exome results from 145 individuals with unexplained JS identified six families with predominantly compound heterozygous mutations in KIAA0586. A c.428del base deletion in 0.1% of the general population was found in trans with a second mutation in an additional set of 9 of 163 unexplained JS patients. KIAA0586 is an orthologue of chick Talpid3, required for ciliogenesis and Sonic hedgehog signaling. Our results uncover a relatively high frequency cause for JS and contribute a list of candidates for future gene discoveries in ciliopathies.
Keywords: Abnormalities, Multiple; Cell Cycle Proteins; Cerebellum; Eye Abnormalities; Gene Frequency; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Heterozygote; Humans; Kidney Diseases, Cystic; Mutant Proteins; Retina; RNA, Small Interfering

CLP1 founder mutation links tRNA splicing and maturation to cerebellar development and neurodegeneration. - Schaffer, Ashleigh E; Eggens, Veerle R C; Çağlayan, Ahmet Okay; Reuter, Miriam S; Scott, Eric; Coufal, Nicole G; Silhavy, Jennifer L; Xue, Yuanchao; Kayserili, Hülya; Yasuno, Katsuhito; Rosti, Rasim Ozgur; Abdellateef, Mostafa; et al. (Cell, 2014)
Neurodegenerative diseases can occur so early as to affect neurodevelopment. From a cohort of more than 2,000 consanguineous families with childhood neurological disease, we identified a founder mutation in four independent pedigrees in cleavage and polyadenylation factor I subunit 1 (CLP1). CLP1 is a multifunctional kinase implicated in tRNA, mRNA, and siRNA maturation. Kinase activity of the CLP1 mutant protein was defective, and the tRNA endonuclease complex (TSEN) was destabilized, resulting in impaired pre-tRNA cleavage. Germline clp1 null zebrafish showed cerebellar neurodegeneration that was rescued by wild-type, but not mutant, human CLP1 expression. Patient-derived induced neurons displayed both depletion of mature tRNAs and accumulation of unspliced pre-tRNAs. Transfection of partially processed tRNA fragments into patient cells exacerbated an oxidative stress-induced reduction in cell survival. Our data link tRNA maturation to neuronal development and neurodegeneration through defective CLP1 function in humans.
Keywords: Animals; Brain; Cerebellum; Cleavage And Polyadenylation Specificity Factor; Female; Humans; Male; Mice; Models, Molecular; Neurodegenerative Diseases; Nuclear Proteins; Pedigree; Phosphotransferases; RNA Splicing; RNA, Transfer; Saccharomyces cerevisiae; Transcription Factors; Zebrafish; Zebrafish Proteins

Exome sequencing links corticospinal motor neuron disease to common neurodegenerative disorders. - Novarino, Gaia; Fenstermaker, Ali G; Zaki, Maha S; Hofree, Matan; Silhavy, Jennifer L; Heiberg, Andrew D; Abdellateef, Mostafa; Rosti, Basak; Scott, Eric; Mansour, Lobna; Masri, Amira; Kayserili, Hülya; et al. (Science, 2014)
Hereditary spastic paraplegias (HSPs) are neurodegenerative motor neuron diseases characterized by progressive age-dependent loss of corticospinal motor tract function. Although the genetic basis is partly understood, only a fraction of cases can receive a genetic diagnosis, and a global view of HSP is lacking. By using whole-exome sequencing in combination with network analysis, we identified 18 previously unknown putative HSP genes and validated nearly all of these genes functionally or genetically. The pathways highlighted by these mutations link HSP to cellular transport, nucleotide metabolism, and synapse and axon development. Network analysis revealed a host of further candidate genes, of which three were mutated in our cohort. Our analysis links HSP to other neurodegenerative disorders and can facilitate gene discovery and mechanistic understanding of disease.
Keywords: Animals; Axons; Biological Transport; Cohort Studies; Exome; Gene Regulatory Networks; Genetic Association Studies; Humans; Motor Neuron Disease; Mutation; Neurons; Nucleotides; Pyramidal Tracts; Sequence Analysis, DNA; Spastic Paraplegia, Hereditary; Synapses; Transcriptome; Zebrafish

Mutations in CSPP1 lead to classical Joubert syndrome. - Akizu, Naiara; Silhavy, Jennifer L; Rosti, Rasim Ozgur; Scott, Eric; Fenstermaker, Ali G; Schroth, Jana; Zaki, Maha S; Sanchez, Henry; Gupta, Neerja; Kabra, Madhulika; Kara, Majdi; Ben-Omran, Tawfeg; et al. (Am J Hum Genet, 2014)
Joubert syndrome and related disorders (JSRDs) are genetically heterogeneous and characterized by a distinctive mid-hindbrain malformation. Causative mutations lead to primary cilia dysfunction, which often results in variable involvement of other organs such as the liver, retina, and kidney. We identified predicted null mutations in CSPP1 in six individuals affected by classical JSRDs. CSPP1 encodes a protein localized to centrosomes and spindle poles, as well as to the primary cilium. Despite the known interaction between CSPP1 and nephronophthisis-associated proteins, none of the affected individuals in our cohort presented with kidney disease, and further, screening of a large cohort of individuals with nephronophthisis demonstrated no mutations. CSPP1 is broadly expressed in neural tissue, and its encoded protein localizes to the primary cilium in an in vitro model of human neurogenesis. Here, we show abrogated protein levels and ciliogenesis in affected fibroblasts. Our data thus suggest that CSPP1 is involved in neural-specific functions of primary cilia.
Keywords: Abnormalities, Multiple; Brain; Cell Cycle Proteins; Centrosome; Cerebellar Diseases; Cerebellum; Cilia; Cohort Studies; Eye Abnormalities; Fibroblasts; Gene Deletion; Humans; Image Processing, Computer-Assisted; Kidney Diseases, Cystic; Microtubule-Associated Proteins; Polymorphism, Single Nucleotide; Retina

Mutations in LAMB1 cause cobblestone brain malformation without muscular or ocular abnormalities. - Radmanesh, Farid; Çağlayan, Ahmet Okay; Silhavy, Jennifer L; Yilmaz, Cahide; Cantagrel, Vincent; Omar, Tarek; Rosti, Basak; Kaymakçalan, Hande; Gabriel, Stacey; Li, Mingfeng; Šestan, Nenad; Bilguvar, Kaya; et al. (Am J Hum Genet, 2013)
Cobblestone brain malformation (COB) is a neuronal migration disorder characterized by protrusions of neurons beyond the first cortical layer at the pial surface of the brain. It is usually seen in association with dystroglycanopathy types of congenital muscular dystrophies (CMDs) and ocular abnormalities termed muscle-eye-brain disease. Here we report homozygous deleterious mutations in LAMB1, encoding laminin subunit beta-1, in two families with autosomal-recessive COB. Affected individuals displayed a constellation of brain malformations including cortical gyral and white-matter signal abnormalities, severe cerebellar dysplasia, brainstem hypoplasia, and occipital encephalocele, but they had less apparent ocular or muscular abnormalities than are typically observed in COB. LAMB1 is localized to the pial basement membrane, suggesting that defective connection between radial glial cells and the pial surface mediated by LAMB1 leads to this malformation.
Keywords: Basement Membrane; Brain; Cerebellum; Cerebral Cortex; Encephalocele; Female; Genetic Predisposition to Disease; Homozygote; Humans; Laminin; Male; Muscular Dystrophies; Nervous System Malformations; Neuroglia; Neurons; Sequence Deletion; Walker-Warburg Syndrome